Analisis Literatur : Faktor Faktor Yang Mempengaruhi Munculnya Sengketa Pajak Penghasilan Pada Perusahaan Perseroan Terbatas Di Indonesia - Hastica, Hintan; Ranatarisza, Mirza Maulinarhadi; Wijaya, Gabrielle Audrey; Sitorus, Dian Gracia; Setiya, Nur Rahmadita (Jurnal Akuntansi dan Pajak, 2025)
Tax disputes are disputes that arise due to discrepancies with the provisions of tax regulations that can have an impact on the company as well as the investment climate and state revenue. This article aims to explore the factors that drive the occurrence of income tax disputes in companies in the form of Limited Liability Companies (PT) in Indonesia in the period 2020 - present. Through a comprehensive review of relevant literature, researchers hope to identify specifically the main causes of tax disputes in companies in the form of Limited Liability Companies (PT). By understanding the root of the problem, it is expected to formulate effective policy recommendations in minimising the occurrence of tax disputes in the future. The results of this study are expected to make a significant contribution in creating a healthier tax climate and increasing investor confidence in the tax system in Indonesia. Keywords: Tax dispute; Limited Liability Company; Income Tax; Emergence of Dispute